Cover Feature: A pH‐sensitive Macromolecular Prodrug as TLR7/8 Targeting Immune Response Modifier (Chem. Eur. J. 70/2017). Issue 70 (16th October 2017) - Aichhorn, Stefan; Linhardt, Anne; Halfmann, Angela; Nadlinger, Markus; Kirchberger, Stefanie; Stadler, Manuela; Dillinger, Barbara; Distel, Martin; Dohnal, Alexander; Teasdale, Ian; Schöfberger, Wolfgang
Abstract : The chemical synthesis and biological activity of new functionalized imidazoquinoline derivatives (ImQ) to generate Toll‐like receptor (TLR) 7/8 specific prodrugs are presented. In vivo activity of ImQs to induce inflammation was confirmed in zebrafish larvae. After covalent ligation to fully biodegradable polyphosphazenes (ImQ‐polymer), the macromolecular prodrugs were designed to undergo intracellular pH‐sensitive release of ImQs to induce inflammation through binding to endosomal TLR7/8. More information can be found in the Full Paper by M. Distel, A. Dohnal, I. Teasdale, W. Schöfberger et al. onpage 17721 .